Charge-neutral nonlocal response in superconductor-InAs nanowire hybrid devices. (6th August 2021) - Denisov, A O; Bubis, A V; Piatrusha, S U; Titova, N A; Nasibulin, A G; Becker, J; Treu, J; Ruhstorfer, D; Koblmüller, G; Tikhonov, E S; Khrapai, V S
Abstract: Nonlocal quasiparticle transport in normal-superconductor-normal (NSN) hybrid structures probes sub-gap states in the proximity region and is especially attractive in the context of Majorana research. Conductance measurement provides only partial information about nonlocal response composed from both electron-like and hole-like quasiparticle excitations. In this work, we show how a nonlocal shot noise measurement delivers a missing puzzle piece in NSN InAs nanowire-based devices. We demonstrate that in a trivial superconducting phase quasiparticle response is practically charge-neutral, dominated by the heat transport component with a thermal conductance being on the order of conductance quantum. This is qualitatively explained by numerous Andreev reflections of a diffusing quasiparticle, that makes its charge completely uncertain. Consistently, strong fluctuations and sign reversal are observed in the sub-gap nonlocal conductance, including occasional Andreev rectification signals. Our results prove conductance and noise as complementary measurements to characterize quasiparticle transport in superconducting proximity devices.